Freshwater sharks and rays - Lucifora, Luis Omar (2015)
Hang on, I thought sharks and rays only live in the ocean? That’s true for about 95%. However, there are species of elasmobranchs (sharks and rays) that occur regularly at low salinities, often beyond the tidal reaches of the sea. These make up around 5% of living elasmobranchs (roughly 56 out of 1154 described species). Species that are confined to freshwaters are termed obligate freshwater species, and comprise all the freshwater stingrays (family Potamotrygonidae) and several stingrays (Dasyatidae). Species that can tolerate a wide range of salinities, from freshwater to brackish and/or marine waters, are termed ‘euryhaline species’. Euryhaline species include sawfishes (Pristidae), several whaler sharks (Carcharhinidae), one skate (Rajidae), and a number of stingrays (Dasyatidae). They range in maximum size from only 20–30 cm disc width in several freshwater stingrays, to at least 6.5 m total length in the Largetooth Sawfish (Pristis pristis).